2006
DOI: 10.1111/j.1525-139x.2006.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

UNRESOLVED ISSUES IN DIALYSIS: Long‐Term Management of the Tunneled Venous Catheter

Abstract: Despite their propensity for significant complications, tunneled central venous catheters have become a common means of vascular access in the United States for patients requiring maintenance hemodialysis for end-stage renal disease (ESRD). Reasons for their use include advanced patient age, peripheral vascular disease (arterial and venous), late referral for creation of vascular access, and more importantly, the lack of an interdisciplinary service line on vascular access among vascular surgeons, radiologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 85 publications
3
51
0
4
Order By: Relevance
“…In addition, some stable patients had acute worsening kidney function that was not predictable, resulting in an urgent need for dialysis. CVC continues to be the most common urgent-start dialysis access, representing approximately 80% of all accesses [3]; however, multiple studies have demonstrated a variety of complications associated with the placement and use of CVC, including catheter-related infections, thromboses, catheter malfunction, and hemodynamic instability, resulting in a negative effect on patient survival [1618]. Lee et al [19] reported that the risk of CVC-related infection is close to 50% by 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some stable patients had acute worsening kidney function that was not predictable, resulting in an urgent need for dialysis. CVC continues to be the most common urgent-start dialysis access, representing approximately 80% of all accesses [3]; however, multiple studies have demonstrated a variety of complications associated with the placement and use of CVC, including catheter-related infections, thromboses, catheter malfunction, and hemodynamic instability, resulting in a negative effect on patient survival [1618]. Lee et al [19] reported that the risk of CVC-related infection is close to 50% by 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…2 Nevertheless, late complications-particularly infection and thrombosis-remain problematic and can lead to catheter dysfunction and significant morbidity. [6][7][8] To the best of the authors' knowledge, no local data yet exist from Oman regarding the safety of radiological catheter placement and the prevalence of catheter-related complications. This study therefore aimed to assess the technical success, safety and immediate and delayed complications of ultrasound-and fluoroscopy-guided TVCs at SQUH.…”
mentioning
confidence: 99%
“…If these therapies do not restore adequate QB, a referral is made to the interventional center for catheter exchange. Current therapy once the patient is referred to the interventional center for dysfunction TDC owing to an inadequate QB is summarized in Table 2 (7).…”
Section: Treatment Of Thrombosis and Fibrin Sheath Formationmentioning
confidence: 99%